The educational policy of the new Brazilian Common National Curriculum Framework: an Analysis based on Biopolitics - Trevisan, Amarildo Luiz (Pro-posições, 2024)
Abstract This article discusses the educational policy of the new Brazilian National Curricular Common Base (NCCB-BNCC) in the epistemological context of biopolitics. It brings together international authors and works that contribute to elucidate elements of this context, such as the concepts of "life" and "death," "citizenship," and "bare life." The text presents the criticisms of some Brazilian educators on the subject, focusing primarily on Dermeval Saviani's diagnosis, one of the important references in the field of Brazilian educational policy. It concludes that such concepts can shed new light on the subject, demonstrating the fragility of this educational policy that, by being exclusively guided by biopolitical criteria, excludes a broader and civic education. Resumen El artículo busca efectuar el debate sobre el tema de la política educativa de la nueva Base Común Curricular Nacional (BCCN) en el contexto epistemológico de la biopolítica. Reúne autores y obras del escenario mundial que contribuyen a dilucidar elementos presentes en este contexto, como los conceptos de “vida” y “muerte”, “ciudadanía” y “vida desnuda”. Presenta las críticas de algunos educadores brasileños sobre el tema, centrándose especialmente en el diagnóstico de Dermeval Saviani, una de las referencias importantes en el campo de la política educativa brasileña. Concluye que tales conceptos pueden arrojar una nueva luz integral sobre el tema abordado, demostrando así la fragilidad de tal política educativa. Al guiarse por criterios exclusivamente biopolíticos, esta excluye una educación ampliada y ciudadana. Resumo O artigo procura efetuar o debate sobre o tema da política educacional da nova Base Nacional Comum Curricular (BNCC) no contexto epistemológico da biopolítica. Agrega autores e obras do cenário mundial que contribuem para elucidar elementos presentes neste contexto, como os conceitos de “vida” e “morte”, “cidadania” e “vida nua”. Apresenta as críticas de alguns educadores brasileiros ao tema, concentrando-se especialmente no diagnóstico de Dermeval Saviani, um dos referenciais importantes da área da política educacional brasileira. Conclui que tais conceitos podem lançar uma nova luz compreensiva sobre o assunto tratado, demonstrando assim a fragilidade de tal política educacional que, ao se pautar por critérios exclusivamente biopolíticos, exclui uma formação ampliada e cidadã.